Development of a Method for Crustacean Allergens Using Liquid Chromatography/Tandem Mass Spectrometry. (27th November 2019) - Nagai, Hiroyuki; Minatani, Tomiaki; Goto, Kotaro
Abstract: An LC/MS/MS analysis method was developed for crustacean allergens, tropomyosin, and arginine kinase. A protein extract from shrimp was reduced, alkylated, and digested by trypsin. Peptide spectra were obtained using full scan analysis by LC/MS/MS, and we determined a sequence through a protein search. 22 ADTLEQQNK 30, 92 IQLLEEDLER 101, 113 LAEASQAADESER 125, 134 SLSDEER 140, 153 FLAEEADR 160, and 190 IVELEEELR 198 of tropomyosin and 152 VSSTLSSLEGELK 164 and 217 TFLVWVNEEDHLR 229 of arginine kinase were selected as the specific peptides, and optimal multiple-reaction monitoring conditions were used. The results obtained through the LC/MS/MS analysis correlated well with those using the ELISA method for various crustacean samples (r 2 > 0.9). Moreover, unregulated species, such as krill or insects, which produce positive results in some crustacean ELISA assays, can be differentiated by LC/MS/MS. These findings suggest that LC/MS/MS analysis may be effective for crustacean food allergen analysis.